Demonstrate, Observe, Assist, and Perform versus structured educational video in imparting standard skill in male urinary bladder catheterization - Balakrishnan, Santosh; Paul, Lijo; N Rajan, Minu; Alias Arthungal, Sherin (Asian Journal of Medical Sciences, 2022)
Background: Conventional teaching-learning methods often fail to assure competency in male bladder catheterization (MBC) in the Indian Medical Graduate. Introduction of structured training methods could offer a solution. Aims and Objectives: The objective of the study was to compare efficiency of demonstrate, observe, assist, and perform (DOAP) method of training in a skill lab against structured educational video (SEV)-based learning in training final MBBS students in the psychomotor skill to safely perform MBC. Materials and Methods: Following IRB and IEC clearance, final MBBS students fulfilling selection criteria were randomly allocated into two comparable groups. One group underwent skill lab training using DOAP method while the other group underwent training using a SEV by the same instructor. CRRI interns, regularly performing MBC at work by virtue of conventional training, with 6–8 months experience formed a control group. All participants underwent assessment of skill in MBC by skill lab OSCE evaluation, by assessors blinded to the participant’s method of training. Data were recorded and analyzed using standard statistical software. Trial evaluation from the trial groups was obtained using SurveyMonkey tool. Results: There was no statistically significant difference in the ability of DOAP group or SEV group to safely perform MBC though a higher level of confidence was expressed with their training by DOAP group. Both trial groups statistically outperformed the control group. Conclusion: Structured training assures competence. Video-assisted training produces comparable results though DOAP method is preferred by students. A combination of the techniques may facilitate optimal training.